Tomato: Breeding and Genomics - Prasanna, HC; Rai, N.; Hussain, Zakir; Yerasu, Suresh R.; Tiwari, Jagesh K. (Vegetable Science, 2023)
Tomato is an important vegetable of the human diet. In tomatoes, through conventional breeding methods, manycultivars with desirable traits have been developed. With the advancement in sequencing technologies combined withreducing cost per sample, high-throughput genotyping platforms and bioinformatics pipelines have revolutionizedtomato improvement. After the tomato genome sequencing in 2012, thousands of cultivated and wild species have beensequenced with respect to studies on population structure, genetic diversity, high-density maps and structural variantsanalysis so on. Now, genomics-assisted research would aim to discover of QTLs/genes and associated SNP markers bygenome-wide association studies (GWAS) using high-throughput genotyping (SNP array or genotyping-by-sequencing)for rapid breeding. Moreover, genome editing and genomics selection tools would increase breeding efficiency andhigher genetic gain in tomatoes.